Analisis Supervisi Berdasarkan Model Triko: Kooperatif, Konsultatif, dan Korektif Guru Sekolah Dasar - Sri Indarwati; Sunarto Sunarto (Universitas Sarjanawiyata Tamansiswa, 2022)
Abstract: Supervision Analysis Based on Cooperative, Consultative, and Corrective Values ​​for Cacaban 1 Elementary School Teachers, Magelang City in 2020/2021. The research objectives include: (1) To determine the supervision process based on the Triko teacher model in the Diponegoro Cluster, Magelang City; (2) To find out the results achieved by supervision management based on the Triko teacher model in Cacaban 1 State Elementary School Magelang City; (3) To find out the supporting factors and inhibiting factors for supervision management based on the Triko teacher model in the Diponegoro Cluster, Magelang City; (4) To find out the inhibiting factors for supervision based on the Triko teacher model in elementary schools throughout in Ccacaban 1, Magelang City; (5) To determine the effect of developing supervision based on the Triko model in elementary schools throughout the Cacaban 1 State Elementary School, Magelang City. This type of research is using qualitative research to determine supervision according to Triko or Ki Hajar Dewantara's teaching model in the , Magelang City. This research uses interview, observation, documentation, and literature techniques. The research was carried out at the Cacaban 1 State Elementary School Magelang City. Data analysis uses the Miles Huberman model which includes data reduction, data display, conclusion drawing and verification. Based on the results of data analysis, it can be concluded: (1) In the management of supervision of the Triko model: cooperative, consultative, and corrective at Cacaban 1 State Elementary School Magelang City involving the Principal and Teachers, the budget is clear, the quantity and quality of school residents is sufficient, planning activities through meeting. (2) Innovation and Creativity in supervision management at Cacaban 1 State Elementary School Magelang City involves Principal and Teachers. The source of funds for supervision creative innovation is very clear. (3) The management of school supervision at Cacaban 1 State Elementary School Magelang City can be concluded that there are no obstacles in planning human resources. Meanwhile, in planning activity financing funds, planning methods/procedures solutions through deliberation or joint discussions between the principal and teachers. Keywords: Supervision, Triko model: cooperative, consultative, and corrective.